Effect of Fist Clenching on Vein Visibility and Palpability - Durmus Iskender, Mahinur; Eren, Handan; Calıskan, Nurcan (Ovid Technologies (Wolters Kluwer Health), 2022)
No information exists on the minimum number of times that fist clenching should be performed to increase vein visibility and palpability. In this study, the researchers aimed to determine the average number and duration of fist clenching to increase vein visibility and palpability before peripheral intravenous catheter insertion. This observational study included 207 healthy individuals. Participants meeting the inclusion criteria were asked to perform fist clenching. The number and duration of fist clenches performed to increase dorsal metacarpal vein and cephalic vein grade were determined. The participants carried out fist clenching 7.57 ± 4.26 times for the first increase and 22.16 ± 7.93 times for the second increase in dorsal metacarpal vein grade. Fist clenching was carried out 10.05 ± 7.30 times for the first increase and 21.30 ± 7.86 times for the second increase in cephalic vein visibility. A statistically significant, weak, but positive relationship was observed between the duration of fist clenching and the change in dorsal metacarpal vein grade and anxiety level (r = 0.194, P < .005). However, the relationship was negative between room temperature and the duration of fist clenching in dorsal metacarpal vein grade (r = –0.207, P = .003). This inexpensive and simple technique should be performed in specified numbers before catheter insertion.
Keywords: Catheterization, Peripheral; Humans; Hand; Veins